The Effectiveness of an ABA Program Based on Behavioral Theory for Improving Desired Behavior in Children with Autism Spectrum Disorder - Mustafa, Iman Mohammed; Ali, Nizar Ismat (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
This study aimed to experimentally verify the effectiveness of Applied Behavior Analysis (ABA) program based on behavioral theory in improving desired behaviors among children with Autism Spectrum Disorder (ASD). The research employed an experimental method with equivalent groups design (experimental and control) using pre-test and post-test measurements. The research population consisted of all children diagnosed with ASD in Duhok Governorate and Zakho Independent Administration in Iraq, from which a purposive sample of 34 children was selected and randomly assigned to experimental (n=17) and control (n=17) groups. The Autism Behavior Rating Scale was used as the primary measurement instrument after establishing its validity and reliability. The ABA program, implemented over 15 weeks through 30 sessions, incorporated comprehensive behavioral strategies including positive reinforcement, shaping, sequencing, and modeling. Results showed significant improvements in the behavioral dimension among the experimental group compared to the control group, while no statistically significant differences were found in the social dimension between groups despite observable improvements. Within-group analysis demonstrated significant improvements in both behavioral and social dimensions for the experimental group when comparing pre-test and post-test scores. These findings confirm ABA's effectiveness in improving desired behaviors among children with ASD, particularly when implemented systematically with individualized adaptations.